SHARIA HOSPITAL BUSINESS DEVELOPMENT STRATEGY FOR ISLAMIC HIGHER EDUCATION IN INDONESIA - Nasution, Muhammad; Tarigan, Azhari; Siregar, Muhammad; Nurbaiti, Nurbaiti; Harahap, Muhammad; Lauli, Rahmad (Faculty of Economics and Business, University of Pasundan, 2024)
This research aims to identify the sharia hospital business development strategy for Islamic Religious Universities in Indonesia (PTKI). This study employs both qualitative and quantitative methods that was conducted at ten sharia hospitals by interviews with experts, sharia hospital practitioners, and sharia hospital regulators. The Analytical Network Process (ANP) method was used to analyze the interview results. The research results stated that the Sharia hospital has great potential to be developed for PTKI in Indonesia because the market potential was wide open and there were still few Sharia hospitals standing, so PTKI must play a role by creating human resources capable of managing a Sharia hospital. Research results should the priority problems in developing the Sharia hospital business within the PTKI environment in Indonesia were regulatory, then capital, human resources, and finally literacy issues. The priorities for the Sharia hospital business development strategy within PTKI in Indonesia were government support, then regulations, strengthening capital, quality, and quantity of human resources, and finally increasing literacy.